A series of persuasive events. Sequencing effects of negative and positive messages on party evaluations and perceptions of negativity. Issue 4 (19th May 2018) - Nai, Alessandro; Seeberg, Henrik Bech
Abstract: We test how party evaluations and perceptions of negativity are affected by sequences of positive/negative persuasive messages. In an experimental survey collected in Denmark, respondents were exposed to either a positive or a negative message on three issues in a random order; this creates a setting where we can test for the effects of eight different sequences of positive and/or negative messages. We find consistent effects. Being exposed to a higher volume of negative messages often depresses evaluations of the target, whereas being exposed to a higher volume of positive messages enhances evaluation of the sponsor. These effects are nuanced by recency effects: when a sequence ends on a negative message, regardless of its overall valence, evaluation of the target is depressed; similarly, negatively valenced sequences harm the target except when the sequence ends on a positive message. Backlash effects are unlikely, and no sequence simultaneously harms the target and promotes a positive evaluation of the sponsor. Finally, negatively valenced sequences of messages enhance perceptions of negativity, whereas positively valenced sequences do not reduce it; this trend is also nuanced by recency effects.